Effect of topical ellagic acid application on titanium implant osseointegration and oxidative stress - Gul, M.; Dundar, S.; Koyuncu, I; Yigin, A.; Tanik, A.; Bingul, M. Bahattin (Ariesdue Srl, 2022)
Aim The aim of our study was to biomechanically evaluate the effect of topical ellagic acid (EA) on implant osseointegration before dental implants were placed in the tibia of rats, its effect on the bone tissue in the dental implant area, and its effect on oxidative stress. Materials and methods In the study, a total of 16 Wistar albino rats each weighing 250-300 g were divided into two equal groups. All rats were placed in standard cages in groups of two animals and fed ad libitum with a normal diet and water. Control group: One 2.5 mm-diameter, 4 mm-long titanium implant was placed in the metaphyseal part of the right tibia bone of each subject (n = 8). Test group (EA): The same surgical procedure as for the controls was applied to each subject (n = 8), and additionally 0.325 mg/kg EA was applied topically to the implant cavity before the implants were placed. Results The biomechanical analysis showed that, although higher values were obtained in bone implant fusion in the EA group than among the controls, no statistically significant difference was found. Oxidative stress index (OSI) values were compared, and statistically significantly lower values were obtained in both blood and bone tissue around the implant. Conclusions It was found that the topical use of EA in dental implant applications has positive effects on implant osseointegration and bone mechanism, thanks to its antioxidant, antibacterial, and anti-inflammatory properties.
Keywords: Dental implants; Ellagic acid; Oxidative stress; Osseointegration